2024
DOI: 10.36253/jopt-15946
|View full text |Cite
|
Sign up to set email alerts
|

Keetia nodulosa sp. nov. (Rubiaceae - Vanguerieae) of West-Central Africa: bacterial leaf nodulation discovered in a fourth genus and tribe of Rubiaceae

Martin Cheek,
Jean Michel Onana

Abstract: Keetia nodulosa Cheek, a cloud forest climber nearly endemic to Cameroon, with a single record from Nigeria, is described and illustrated. It is remarkable as the first known species to be recorded with bacterial leaf nodules (BLN) in the genus Keetia, and also, in the tribe Vanguerieae. Other genera in Rubiaceae with BLN are Psychotria (Psychotrieae-Rubioideae), Sericanthe (Coffeeae) and Pavetta (Pavetteae), both Ixoroideae/Dialypetalanthoideae. The BLN in Keetia (Vanguerieae) are illustrated for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…The case of Afrothismia ugandensis , formerly included in the apparently greatly disjunct Cameroon/Gabon species A. winkleri (albeit recognised as varietally different), suggests that it might repay effort to reexamine other such cases of apparently far disjunct species with this range. A recent re-assessment of another such disjunct species (western Uganda and Cameroon) species, Keetia purseglovei Bridson (Rubiaceae), showed that the Cameroon material was a separate species from the Ugandan (Cheek & Onana 2024). A further example of an apparently widespread and Cameroon/Ugandan disjunct taxon, Dovyalis spinosissima Gilg (Salicaceae) also led to the recognition of distinct species in both countries after further taxonomic study (Cheek & Ngolan 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The case of Afrothismia ugandensis , formerly included in the apparently greatly disjunct Cameroon/Gabon species A. winkleri (albeit recognised as varietally different), suggests that it might repay effort to reexamine other such cases of apparently far disjunct species with this range. A recent re-assessment of another such disjunct species (western Uganda and Cameroon) species, Keetia purseglovei Bridson (Rubiaceae), showed that the Cameroon material was a separate species from the Ugandan (Cheek & Onana 2024). A further example of an apparently widespread and Cameroon/Ugandan disjunct taxon, Dovyalis spinosissima Gilg (Salicaceae) also led to the recognition of distinct species in both countries after further taxonomic study (Cheek & Ngolan 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The format of the description follows those in other papers describing new species of Keetia , e.g. Cheek & Bridson (2019), Cheek & Onana (2024). Terminology follows Beentje & Cheek (2013).…”
Section: Methodsmentioning
confidence: 99%
“…(2017), Cheek et al . (2018a), Cheek & Bridson (2019) and Cheek & Onana (2024), and several other taxa that fit no other species, (e.g. Cheek et al 2004; 2011)) remain to be described.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations